Measuring the Relationship Between Oil Revenues and the Parallel Exchange Rate in Iraq for the Period (2003-2023): An Empirical Study - Salim, Saif; al-Bakri , Safaa (Journal of Economics and Administrative Sciences, 2025)
This study is an empirical investigation into the relationship between oil revenues and the parallel exchange rate in Iraq during the period from 2003 to 2023, highlighting the susceptibilities of a rentier economy dependent overwhelmingly on oil exports. The study adopted a deductive procedure coupled with econometric analysis using the Autoregressive Distributed Lag (ARDL) method to analyze the impacts of oil revenues and GDP without oil on the parallel exchange rate. Annual data were gathered from official Iraqi agencies and subjected to unit root tests, bounds cointegration tests, and error correction model (ECM) tests. The results indicate a statistically significant long-term negative relation between oil revenues and the parallel exchange rate, meaning that as oil revenues increase, the exchange rate appreciates. In the same vein, GDP without oil was also found to exert a negative influence on the parallel exchange rate, illustrating how the non-oil sector is crucial to the stabilization of the economy. Describing how fluctuations in oil revenues induced exchange rate dynamics, the results also accentuated the need for exchange rate stabilization through diversification and sound oil revenue management. These inferences are instructive for policymakers who endeavor to stabilize the exchange rate and promote sustainable economic development in resource-dependent economies like Iraq.